2008
DOI: 10.1063/1.2996350
|View full text |Cite
|
Sign up to set email alerts
|

The roles of electronic exchange and correlation in charge-transfer-to-solvent dynamics: Many-electron nonadiabatic mixed quantum/classical simulations of photoexcited sodium anions in the condensed phase

Abstract: The charge-transfer-to-solvent (CTTS) reactions of solvated atomic anions serve as ideal models for studying the dynamics of electron transfer: The fact that atomic anions have no internal degrees of freedom provides one of the most direct routes to understanding how the motions of solvent molecules influence charge transfer, and the relative simplicity of atomic electronic structure allows for direct contact between theory and experiment. To date, molecular dynamics simulations of the CTTS process have relied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 81 publications
1
45
0
Order By: Relevance
“…Femtosecond X-ray absorption spectroscopy at the I L-edges detected the birth of the neutral halogen, but the time resolution was not sufficient to capture the early dynamics 7 . Of particular relevance here are the studies by Ruhman et al 11,12 and Schwartz et al 13,14,[22][23][24][25] on the CTTS states of sodide (Na À ) in tetrahydrofuran (THF) and ether solvents, which enabled them to probe at high-time resolution both the signal of the ejected electron and the nascent neutral sodium atom. They found that electrons photodetached from the parent ion appear with their equilibrium spectrum after 500 fs with no further spectral evolution, nor a pump wavelength dependence.…”
mentioning
confidence: 99%
“…Femtosecond X-ray absorption spectroscopy at the I L-edges detected the birth of the neutral halogen, but the time resolution was not sufficient to capture the early dynamics 7 . Of particular relevance here are the studies by Ruhman et al 11,12 and Schwartz et al 13,14,[22][23][24][25] on the CTTS states of sodide (Na À ) in tetrahydrofuran (THF) and ether solvents, which enabled them to probe at high-time resolution both the signal of the ejected electron and the nascent neutral sodium atom. They found that electrons photodetached from the parent ion appear with their equilibrium spectrum after 500 fs with no further spectral evolution, nor a pump wavelength dependence.…”
mentioning
confidence: 99%
“…These characteristically blue solutions are now fabricated to control the amount of metal ions, including metal anions. Such solutions have been extensively studied for use in organic synthesis and elucidation of charge-transfer to solvent dynamics (CTTS) [2][3][4][5][6][7][8][9]. In the gas phase, a beam of positively charged alkali cations created from metal vapor can undergo double electron capture to generate a low density negative ion beam [10].…”
mentioning
confidence: 99%
“…However, unlike electronic structure methods based on Gaussian basis functions, our 2EFG method can easily capture electronic wave functions that are localized away from atomic cores, such as the CTTS states of atomic anions, 11 as also demonstrated in detail in Paper II. We also demonstrated that the 2EFG method can handle molecular systems by calculating the PECs of the sodium dimer to a similar level of accuracy as a full CI calculation that used Gaussian basis functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Alavi used PIB states to study the properties of two interacting electrons in a box. 11 As shown in the Supporting Information, 31 our 2EFG method is related to our previous real-space CI method. In addition, we previously developed a real-space CI method 10 and used it to study the hydrated dielectron [35][36][37] and aqueous sodide.…”
Section: B Comparison To Other Grid-based Many-electron Wave Functiomentioning
confidence: 99%
See 1 more Smart Citation